PENERAPAN COMPUTER SCIENCE UNPLUGGED PADA MATA PELAJARAN PEMROGRAMAN DASAR TERHADAP PENINGKATAN COMPUTATIONAL THINKING SISWA - Fauziah Dharmawanti, - (2022)
This research is motivated by the importance of Computational Thinking skills in vocational students, especially those in Basic Programming subjects. This ability is very necessary because to implement a case into a programming language it is necessary to describe the flow of computational thinking in the case, so there needs to be a way to train and improve students' Computational Thinking. One way that can train Computational Thinking skills is by applying Unplugged Computer Science learning. Therefore, the purpose of this study is to design and implement Computer Science Unplugged learning in basic programming subjects for sorting material and to determine the effect of Computer Science Unplugged on increasing students' Computational Thinking. The research method used is a quantitative method, with a sample of class XI RPL 4 students at SMK Negeri 2 Sumedang. From this study, the following results were obtained: (1) Learning Computer Science Unplugged can improve students' Computational Thinking abilities which is obtained from the average gain index of 0.53 with "Medium" effectiveness criteria. (2) There is a positive relationship or correlation between learning Computer Science Unplugged and Computational Thinking. (3) Students gave good responses to Computer Science Unplugged learning with an overall average percentage of 84.78%.